Interventional Study to Strengthen The “Adolescent Friendly Health Services” In Anganwadis of Ahmedabad Municipal Corporation - Chauhan, Sandeepkumar R; Dalal, Arohi P; Shukla, Aparajita A (National Journal of Community Medicine, 2012)
Background: Numerous health and information needs of adolescents remain ignored due to constraints at different levels of health care system. One of the effective measures can be strengthening Anganwadis to meet these needs, so that better health and health seeking behavior can be expected. So, the study was carried out with objectives to assess baseline knowledge and practices of AFHS in Anganwadi workers (AWWs), to impart skill-based training to AWWs, to evaluate improvement in knowledge and skills of AWWs at appropriate interval, to assess health status and KAP of Adolescent girls (AGs) of Anganwadis. Methods: Pre-Intervention, a questionnaire was filled up to evaluate knowledge regarding AFHS of 111 AWWs. Training (lecture) on importance of Adolescent health to all 111 AWWs was imparted. Evaluation after 1 & 6 months with same questionnaire was done. Intensive skill-based training to 8 AWWs at their respective Anganwadis was given. General health check-up of AGs of these Anganwadis initially by trainers and then by AWWs was carried out. Improvement in skills was evaluated by observation. Results: Mean age of AWWs was 39.04+7.815years. Mean work-experience was 8.57+8.93years. Mean score pre-intervention, post-intervention-1 month & post-intervention-6 months were 21.68, 34.12 & 36.33 (Total 56) respectively. (ANOVA-test:F=116.32,p<0.0001). 81.69% girls were undernourished, 57.04% showed pallor. Health seeking behavior was poor. Satisfactory improvement was observed in AWWs regarding health check-up of AGs. Communication skills also improved in form of better history taking regarding menstruation, diet and effective health education. Conclusion: Pre-induction & regular skill-based training of AWWs, regular meetings & focused-group discussions with AGs and their mothers are recommended.